Utilization of Schizochytrium mangrovei PQ6 as feed for rotifer Brachionus plicatilis in rearing black sleeper’s larvae (Bostrichthys sinensis, Lacepede, 1881) - Cong, Pham Thanh; Anh, Hoang Thi Lan; Hong, Dang Diem (Academia Journal of Biology, 2019)
Schizochytrium mangrovei PQ6 contains many important polyunsaturated fatty acids, such as docosahexaenoic acid (DHA, C22: 6w-3), eicosahexaenoic acid (EPA, C20: 5w-3) and docosapentaenoic acid (DPA, C22: 5w-6). These fatty acids are essential for survival and growth of many marine fish larvae. In this paper, fresh biomass of S. mangrovei PQ6 was used for culturing rotifer Brachionus plicatilis. In the first formula (L1), rotifers were fed on baker’s yeast; in second formula (L2), rotifers were fed on mixed two microalgae, Nannochloropsis oculata and Chaetoceros gracilis; in the third formula (L3), rotifers were fed on S. mangrovei PQ6 biomass. The results indicated that S. mangrovei PQ6 biomass can replace baker’s yeast and autotrophic microalgae in feeding rotifers. Total lipid, total fatty acid and polyunsaturated fatty acid contents of rotifers fed on formula 3 (S. mangrovei PQ6) were higher than those within others. High polyunsaturated fatty acid (C ≥ 20) in omega-3 and 6 groups; DHA and DPA contents of rotifers fed on S. mangrovei PQ6 were the highest, accounting for 39.81% of total fatty acid; 41.95% and 8.24% polyunsaturated fatty acids, corresponding to 20.52; 12.15 and 2.4 mg/g of dried weight, respectively. The survival rate of black sleeper’s larvae was highest when they were fed on rotifers grown on L3 formula (51.20 ± 0.89%), followed by L2 formula (48.70 ± 2.67%) and the lowest with L1 formula (43.44 ± 1.54%) (P < 0.05). However, among three formulas, no significant difference was found in the growth of black sleeper’s larvae (P > 0.05). These results suggest that biomass of S. mangrovei PQ6 can replace traditional feed like autotrophic microalgae or baker’s yeast for biomass culture of the Brachionus plicatilis rotifer for rearing black sleeper’s larvae to enhance seed quality to meet demands of market.